Developing an Educational Game about the Nusantara Kingdom Using the Game Development Life Cycle Method - Qunita Afif; Aidil Primasetya Armin (Jurnal Teknologi Riset Terapan, 2025)
Purpose:  This study aims to develop a history-based educational game themed on the Nusantara Kingdoms as an alternative learning medium for fourth-grade elementary school students and to evaluate its effectiveness and usability. Research Methodology: The study was conducted at MI Muhammadiyah 25 Surabaya involving 51 fourth-grade students. The game was developed using the Game Development Life Cycle (GDLC) method, which includes initiation, pre-production, production, testing, beta, and release stages. Unity was used as the game engine to develop a puzzle platformer educational game. Data collection techniques included Black Box Testing to evaluate system functionality and White Box Testing to analyze the internal logic and program flow, pre-test and post-test analyzed using the N-Gain method to measure learning improvement, and the System Usability Scale (SUS) questionnaire for usability evaluation. Results: The results of Black Box Testing indicate that all game features functioned properly. Learning effectiveness analysis shows an improvement in students’ understanding of historical material, with an average N-Gain score of 0.335 (34%), categorized as medium improvement. The SUS evaluation produced an average score of 70.59, indicating acceptable usability. Conclusions: The developed educational game is effective, functional, and easy to use for elementary school students. Limitations: This study involved a limited number of participants from one school, focused only on Nusantara Kingdoms material, and the game is available only on the Windows platform. Contributions: This research contributes an interactive GDLC-based educational game as an alternative history learning medium for elementary education.